Muscle Activation and Strength in Squat and Bulgarian Squat on Stable and Unstable Surface - Andersen, V.; Fimland, M. S.; Brennset, Ø.; Haslestad, L. R.; Lundteigen, M. S.; Skalleberg, K.; Saeterbakken, A. H. (International Journal of Sports Medicine, 2014)
The aim of the study was to compare muscle activity using the same relative resistance in squats and Bulgarian squats on stable and unstable surface. Muscle strength and activity were assessed by 6-repetition maximum and concomitant surface electromyography. A cohort of 15 resistance-trained males performed the exercises on the floor or a foam cushion in randomized order. The muscle activity was greater in biceps femoris (63–77%, p<0.01) and core muscle external obliques (58–62%, p<0.05) for the Bulgarian squat compared to regular squats, but lower for rectus femoris (16–21%, p<0.05). Only Bulgarian squat showed differences concerning the surface, e. g. the unstable surface reduced the activation of erector spinae (10%, p<0.05) and biceps femoris (10%, p<0.05) compared to a stable surface. There were similar activations in the vasti muscles and rectus abdominis between the different exercises (p=0.313–0.995). Unstable surfaces resulted in a load decrement of 7% and 10% compared to stable surfaces (p<0.001). In conclusion, the squat was somewhat favorable for the activation of agonists, whereas Bulgarian squat was advantageous for the antagonist and somewhat for core muscles. Bulgarian- and regular squats complement each other, and it may be useful to include both in a periodized resistance training program.
Keywords: EMG; resistance training; core; bilateral; unilateral; instability